Preparation of Vanillic Acid-Loaded Core–Shell Gold Nanospheres/Mesoporous Silica Nanoparticles for the Treatment of Orthopedic Infection - Huang, Yu (ACS Omega, 2021)
[Image: see text] Orthopedic infection is a serious complication in surgeries and remains a great challenge in clinics. Here, the natural antimicrobial compound vanillic acid-loaded gold nanospheres/mesoporous silica nanoparticles (VA@Au-MSNs) were fabricated for chemo-photothermal synergistic therapy to orthopedic infections. The shape and morphology of Au-MSN and VA@Au-MSN were observed by scanning electron microscopy and transmission electron microscopy. The properties of VA@Au-MSN or related components were characterized by dynamic light scattering, thermogravimetric analysis, Brunauer–Emmett–Teller (BET) analysis, and photothermal analysis. Vanillic acid released from VA@Au-MSN was detected in phosphate-buffered saline. A cytotoxicity test and an antibacterial assessment were performed to explore the biosafety and antibacterial activity of VA@Au-MSN, respectively. The results showed that Au-MSN possessed a high BET surface area (458 m(2)/g). After loading vanillic acid, the BET surface area reduced to 72 m(2)/g. The loading efficiency of Au-MSN was 18.56%. Under 808 nm laser irradiation, the temperature at the wound site injected with the Au-MSN solution in the mouse increased from 24 to 60 °C within about 12 s. Also, the high temperature could promote the release of vanillic acid from VA@Au-MSN. Additionally, VA@Au-MSN has no obvious cytotoxicity to MC3T3-E1 cells, but the generated local hyperthermia and the VA released from VA@Au-MSN had excellent antibacterial activity against Staphylococcus aureus in a synergistic way. In conclusion, the VA@Au-MSN with biosafety and excellent antibacterial performance might be applied for the treatment of orthopedic infection.